Impact of Grape Variety, Yeast and Malolactic Fermentation on Volatile Compounds and Fourier Transform Infrared Spectra in Red Wines - Anna Stój; Tomasz Czernecki; Bożena Sosnowska; Agnieszka Niemczynowicz; Arkadiusz Matwijczuk (Polish Journal of Food and Nutrition Sciences)
Volatile compounds are very important to the flavour and quality of the wine. The study aimed to determine the effect of grape variety (Rondo and Zweigelt), yeast, malolactic fermentation (MLF) and yeast×MLF interaction on the content of volatile compounds in red wines. The wines were produced by sequential inoculation with five commercial yeast strains and a commercial lactic acid bacteria (LAB) strain (induced malolactic fermentation) as well as by inoculation with five commercial yeast strains and without LAB inoculation (spontaneous malolactic fermentation). The volatile compounds were determined by headspace solid-phase microextraction/gas chromatography-mass spectrometry (HS-SPME-GC/MS). Forty-six volatile compounds belonging to alcohols, esters, acids, aldehydes, ketones, furan compounds, sulfur compounds and volatile phenols were identified in the wines. The grape variety was the factor with a significant impact on the highest number of volatile compounds, 32 out of 46. Furthermore, 7 compounds were affected by yeast, 10 by MLF and only 3 by yeast×MLF interaction. Characteristic bands in Fourier transform infrared (FTIR) spectra were assigned to the vibrations of functional groups of volatile compounds. The whole FTIR spectra were analysed in detail; three characteristic spectral ranges such as 3650-2700, 1750-1500, and below 1500 cm -1 were shown for different classes of volatile compounds. The most remarkable spectral changes were observed for the last two areas.